Trichoderma virens XZ11-1 producing siderophores inhibits the infection of Fusarium oxysporum and promotes plant growth in banana plants - Haiyang Cui; Qifeng Cheng; Tao Jing; Yufeng Chen; Xiaojuan Li; Miaoyi Zhang; Dengfeng Qi; Junting Feng; Farinaz Vafadar; Yongzan Wei; Kai Li; Yankun Zhao; et al. (Microbial Cell Factories)
Abstract Background Banana Fusarium wilt caused by Fusarium oxysporum f. sp. cubense is a soil-borne fungal disease. Especially, tropical Race 4 (Foc TR4) can infect almost Cavendish subgroup and has a fatal threat to banana industry. Use of antagonistic microbes to manage soil-borne pathogen is viewed as a promising strategy. Results Strain XZ11-1 isolated from tropical rainforest has the production ability of high siderophore. By the analysis of physiological and biochemical profiles, construction of phylogenetic tree, and comparative results from the NR database, strain XZ11-1 was identified as Trichoderma virens. A relative content of 79.45% siderophores was produced in the optimized fermentation solution, including hydroxamate and carboxylate-type siderophores. Siderophores were key for inhibiting the growth of Foc TR4 by competing for environmental iron. Similarly, T. virens XZ11-1 also had antagonistic activities against 10 phytopathogenic fungi. Pot experiments demonstrated that T. virens XZ11-1 could colonize in the root system of banana plants. The symbiotic interaction not only improve plant resistance to Foc TR4, but also enhance iron absorption of roots to promote plant growth by secreting siderophores. Conclusions T. virens XZ11-1 with the high-yield siderophores was isolated and identified. The strain could effectively inhibit the infection of Foc TR4 in banana roots and promote plant growth. It is a promising biocontrol agent for controlling fungal disease.